Investigating the psychometric properties of the Parent Support Partner Outcome Tool. Issue 1 (2nd January 2023) - Williams, Briana J.; Poole, Lindsay; Esterer, Madeline; Carlson, John S.; Batsche-McKenzie, Kim; Tate, Justin; Shank, Jane
ABSTRACT: Parent-to-parent mental health treatment approaches demonstrate a solid evidence base, though a tool to measure changes associated with this innovative service delivery approach has yet to appear in the literature. The Parent Support Partner (PSP) Outcome Tool was developed to evaluate a statewide parent-to-parent service for families of children presenting severe emotional and behavioral challenges. This study explored the factor structure and reliability of the PSP Outcome Tool . Participants were 1, 502 Medicaid-eligible parents of children between the ages of 5–19 with SED (82%), I/DD (12%), or both SED and I/DD (5%) who enrolled in and participated in PSP Services across the state of Michigan from 2017 to 2020. Exploratory factor analysis revealed a three-factor solution (Bridging Collaborative Relationships, Empowerment, Navigating Resources). Cronbach's alpha was high (0.95) for the resulting 23-item outcome tool, and the three factors (i.e. Bridging Collaborative Relationships = 0.91, Empowerment = 0.90, Navigating Resources = 0.84). The factor structure of the scale and the need to establish additional validity support (i.e. predictive, convergent, divergent validity) for its use with diverse groups of parents are discussed.